Leisure Luxuries and the Labor Supply of Young Men - Aguiar, Mark; Bils, Mark; Charles, Kerwin Kofi; Hurst, Erik (Journal of Political Economy, 2021)
We propose a methodology exploiting time diary data and “leisure Engel curves” to infer quality changes across leisure activities and measure the effects on the marginal return to leisure. We study leisure returns for men aged 21–30, who have shifted leisure toward video gaming and recreational computing and have had larger market work hour declines than older men or women since 2004. We show that recreational computing is distinctly a leisure luxury for younger men. By increasing the value of time, innovations to this leisure technology have lowered young men's work hours by 2%, or much of their work hours decline compared to older men's.